A Limit Theorem for Integral Functionals of an Extremum of Independent Random Processes - Matsak, I. K. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We prove a theorem on the convergence of integral functionals of an extremum of independent stochastic processes to a degenerate law of distributions.